Penta Helix Model in Advancing Rural Tourism Development, A Case Study of Padangan Village, Bojonegoro Regency, Indonesia - Baucokro, Ahmad Haddad; Siregar, Johannes Parlindungan; Wicaksono, Agus Dwi (Jurnal Pembangunan dan Alam Lestari, 2025)
The decreasing number of tourists in Padangan Village highlights issues among policymakers. One of the commonly used models to analyze the role of policymakers is the Penta Helix Model. This study aimed to identify the role of Penta Helix actors in developing the tourism sector of Padangan Village. The research employed a descriptive-qualitative approach with a focus on policymakers. Data were collected through in-depth interviews using the snowball sampling method to identify respondents. The findings showed that the most critical role in tourism development in Padangan Village was played by the government, including the Village Head of Padangan, the Department of Tourism and Culture of Bojonegoro, and the Department of Public Works and Housing of Bojonegoro. The roles of media actors and business actors were relatively minor, and collaboration between the government and these groups had not yet been established. Their lack of interest led to the non-involvement of community actors and academics. Meanwhile, tourism development efforts by the actors primarily focused on enhancing attraction components and tourism activities, without paying enough attention to amenities, accessibility, and accommodations. Keywords: Tourism Development; Penta Helix; Stakeholders.